An investigation on mechanical and microstructural properties of hybrid fiber reinforced concrete with manufactured sand and recycled coarse aggregate. (15th June 2023) - Sharma, Rachit; Senthil, K.
Abstract: The emergence of Manufactured Sand (M-Sand) as an alternative to River Sand (R-Sand) and efforts for Recycled Coarse Aggregates (RCA) has opened new opportunities for sustainable growth in urban cities. As a result, M-Sand (100%) and RCA (25%) as sustainable replacement constituents for R-sand and natural coarse aggregates in concrete were utilized to study the mechanical and microstructural properties. The fiber-reinforced concrete with hybrid fibers (steel fiber (SF) + polypropylene fiber (PPF)) was characterized under compression, tension, and flexure. The M-Sand was procured from the local supplier whereas the RCA was prepared in the laboratory employing the treatment using micro silica powder after the mechanical treatment. Overall, it was observed that the synergic use of M-Sand and RCA reduced the workability of concrete. The highest percentage enhancement in compressive and tensile strength on the mix containing M-sand and hybrid (SF (0.75% + PPF (0.1%)) was 27.91% and 57%, respectively as compared to the control mix. The highest flexural toughness (1735%) was observed for concrete containing M-sand and hybrid (SF (0.75% + PPF (0.2%)). The static and dynamic modulus of elasticity of concrete was found to increase with the increase of the percentage of hybrid fiber in the concrete along with M-Sand and RCA. The microstructural analysis indicates significant enhancements for the concrete mix containing M-Sand and treated RCA. Also, it was observed from X-ray diffraction analysis that the peak intensity of quartz in the mix combination of M-Sand and RCA was found to be higher as compared to other mixes which contribute to the higher strength. It is concluded that M-sand contributes to the performance equivalent to the natural fine sand and is found to be a more economical concrete mix with similar Global warming potential and embodied energy characteristics. Highlights: The synergic use of M-Sand and RCA reduce the workability of concrete. The compressive and tensile strength of concrete increased using of M-Sand and RCA. The flexural strength on concrete with M-sand and treated RCA was increased marginally. The static and dynamic modulus of concrete with M-sand and RCA found increased significantly. The concrete using M-Sand and treated RCA has significant enhancements to the microstructure and packing.